PENGARUH STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVINING PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Munthe, Kornel; Ginting, Ribka Diana Br (UNIKA Santo Thomas, 2023)
ABSTRACT This study aims to analyze the effect of institutional ownership and managerial ownership on firm value with profitability as the intervening variable. The data in this study used annual reports from 16 banking companies listed on the Indonesia Stock Exchange from 2016 to 2020. The data collection technique used a purposive sampling technique obtained from the website www.idx.co.id and each website from a sample company. Data processing uses a panel data regression model. The results of the study reveal that institutional ownership has a positive and significant effect on profitability while managerial ownership has a positive and insignificant effect on profitability. Institutional ownership and profitability have a positive and significant effect on firm value and managerial ownership has a positive and insignificant effect on firm value. Profitability is able to mediate institutional ownership of firm value, but profitability is unable to mediate managerial ownership of firm value.